Epac: A Promising Therapeutic Target for Vascular Diseases: A Review - Pan, Yunfeng; Liu, Jia; Ren, Jiahui; Luo, Yun; Sun, Xiaobo (Frontiers in Pharmacology, 2022)
Abstract Vascular diseases affect the circulatory system and comprise most human diseases. They cause severe symptoms and affect the quality of life of patients. Recently, exchange proteins directly activated by cAMP (Epac), have attracted increasing scientific interests since being identified, because of their role in cyclic adenosine monophosphate (cAMP) signaling, a well-known signal transduction pathway. The role of Epac in cardiovascular disease and cancer is extensively studied while the role in kidney disease is less explored. In this study, we aimed to review recent studies on the regulatory effects of Epac on various vascular diseases, such as cardiovascular disease, cerebrovascular disease, and cancer. Accumulating evidence has shown that both Epac1 and Epac2 play important roles in vascular diseases under both physiological and pathological conditions. There has been an increasing focus on the development of inhibitors and activators of Epac. Therefore, we speculated that Epac could serve as a novel therapeutic target for the treatment of vascular diseases.